(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze teachers’ perspectives on the implementation of deep learning as an innovative approach in Social Studies (IPS) learning in elementary schools. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research subjects were selected using purposive sampling, consisting of elementary school six teachers who teach Social Studies. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that teachers have a relatively good understanding of the concept of deep learning, particularly in terms of conceptual understanding, active student engagement, and the relevance of learning materials to real-life contexts. Furthermore, teachers demonstrate positive perspectives toward deep learning as an innovative approach that promotes more interactive, participatory, and contextual learning processes. However, the implementation of deep learning has not been optimal due to several challenges, including limited teacher competence in designing appropriate learning strategies, time constraints, and inadequate learning facilities and infrastructure. In conclusion, deep learning has significant potential to improve the quality of Social Studies learning in elementary schools. However, its successful implementation requires support in the form of enhanced teacher competencies and adequate learning resources.